ACTIVITY TEST OF ETHANOLIC EXTRACT FROM SEMBUNG’S ROOT (BLUMEA BALSEMIFERA[L/]/DC) ON INCREASING APPETITE OF WISTAR FEMALE MICE - Sunarti; Pramukantoro, Ganet Eko (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Empirically, root of Sembung can be used as an appetite enhancer/booster. Increasing appetite effect could be seen from increasing animal body weight and reducing leftover food every time-observation. The aim of this study was to analysis of ethanolic extract of Sembung’s root on increasing appetite that exposured in Wistar female mice. Methods: This research was laboratory experimental which used 25 female Swiss Wistar. Rats, then, were randomly divided into 5 groups (n=5) , CMC 0.5%, normal control, ethanolic extract from sembung’s rootdose II 600 mg/kg body weight, dose II 1200 mg/kg body weight, dose III 1800 mg/kg body weight). Tests conducted for 14 days with 2 parameters: weight gain and the remaining amount of feed. The second parameter is then calculated AUC of total body weight and food scraps. Data was analyzed using statistical test of one-way ANOVA. Results:The results shown that ethanolic extract of root of Blumea balsamifera (L.) DC could increase that the AUC value of the averagebody weight with average Dose I: 199.51 Â± 6.19, Dose II: 198.26Â±9.35, Dose III: 196.81 Â± 7.58, negative control: 187.71 Â± 3.79and normal control: 187.64 Â± 5.00. While the average AUC value of the remaining amount of food at first dose was 10.94 Â± 1.96 showed the lowest value. ANOVA test presented significant value (P <0.05) in reducing amount of leftover food and increasing body weight. Conclusion: Exposuring of ethanolic extract of Sembung’s root Blumeabalsamifera (L.) DC indicated increasing appetite behaviour of female Wistar rats. Â